PDGFRs expression in dogs affected by malignant oral melanomas: correlation with prognosis. (1st February 2016) - Iussich, S.; Maniscalco, L.; Di Sciuva, A.; Iotti, B.; Morello, E.; Martano, M.; Gattino, F.; Buracco, P.; De Maria, R.
Abstract: Canine malignant melanoma (CMM) is the most common canine oral tumour, and up to 70–75% of dogs in stage II–III die within 1 year after surgery. The purpose of this study was to evaluate the expression of platelet‐derived growth factors receptors (PDGFR)‐ α and ‐ β in stage II and III CMMs and to correlate it with prognosis. PDGFRs expression was evaluated by immunohistochemistry on 48 cases of formalin‐fixed CMM samples and correlated with clinical–pathological findings and outcome after surgery. PDGFRs co‐expression was observed in 37.5% of cases. Positivity for PDGFR‐ α and ‐ β receptor was present in 54.2 and 47.9% of cases, respectively. Ki67 values >19.5% were ascertained in 66.7% of cases. Statistical analysis showed that PDGFRs co‐expression and Ki67 values > 19.5% were both associated with worse prognosis. PDGFRs expression suggests a role in the pathogenesis and progression of CMM, and α and β co‐expression appears to be associated to worse prognosis.